2015
DOI: 10.1021/acs.cgd.5b00905
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Amide-Pseudo Amide Hydrogen Bonding Motif within a Series of Theophylline:Amide Cocrystals

Abstract: The pharmaceutically active compound theophylline (T) was cocrystallized with the amides formamide (1), acetamide (2), N-methylformamide (3), N,N-dimethylformamide (4), benzamide (5), and pyrazinamide (6), with systems T:1, T:5, and T:6 displaying polymorphic behavior. The cocrystals with formamide (T:1), acetamide (T:2), and benzamide (T:5), and one polymorph of the cocrystal with pyrazinamide (T:6-I), contain an R 2 2 (9) hydrogen bonding motif between the amide cocrystal formers and the HN−C−CO moiety of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…The tool is based on occurrences of various H-bonded synthons in the Cambridge Structural Database containing more than 1,000,000 crystal structures of small organic and organometallic compounds [ 30 ]. The tool was previously applied for analysis of H-bonding systems in some drug molecules [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The results of ranking synthons by propensity for the favipiravir molecule are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The tool is based on occurrences of various H-bonded synthons in the Cambridge Structural Database containing more than 1,000,000 crystal structures of small organic and organometallic compounds [ 30 ]. The tool was previously applied for analysis of H-bonding systems in some drug molecules [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The results of ranking synthons by propensity for the favipiravir molecule are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Cocrystals containing pyrazinamide with carboxylic acids (Abourahma et al, 2015;Adalder et al, 2012;Kulla et al, 2016;Luo and Sun, 2013), with haloperfluorinated compounds (Choquesillo-Lazarte et al, 2017), with hydrochlorothiazide (Wang et al, 2014), with pyrogallol (Thakuria et al, 2012) and with diflunisal (Évora et al, 2011) have been described. Several polymorphs of cocrystals of PZA with succinic acid (Cherukuvada and Nangia, 2012;Luo and Sun, 2013), malonic acid (Kulla et al, 2017) and theophylline (Eddleston et al, 2015) have been found and investigated. Different binary mixtures leading to either cocrystals or eutectic systems have been described by Rajbongshi et al (Rajbongshi et al, 2018).…”
Section: Literature Data On the Phase Behavior Of Pyrazinamidementioning
confidence: 99%
“…S1-S5 of the supporting information. 2013; Lou et al, 2015;Wang et al, 2014Wang et al, , 2015Abourahma et al, 2011;Luo & Sun, 2013;Eddleston et al, 2016;Aree & Chaichit, 2009;Adalder et al, 2012;Aakerö y et al, 2004;Grobelny et al, 2011;Thakuria et al, 2012;Abourahma et al, 2015;McMahon et al, 2005;Thorat et al, 2015). From the structural analysis of the reported cocrystals it was observed that acid-pyridine (synthon I), acid-acid, amideamide and acid-amide dimers (synthon II, III and IV, respectively) are more common for cocrystals of Pyz containing coformers with acid functionality.…”
Section: Pyzá24dhbamentioning
confidence: 99%